Mutagenesis technology ethyl Methane Sulfonate (EMS) and cow manure application interval on growth and production cucumber (Cucumis sativa L.) - Gulo, Ali Momon; Saragih, Wismaroh Sanniwati; Oesman, Roswita (Central Research Institute For Agriculture, 2024)
This research aims to determine the effect of mutation induction of Ethyl Methane Sulfonate (EMS) and the time interval for applying cow manure to increase cucumber growth and yield. The research was conducted in the experimental field of the Faculty of Agriculture, Universitas Pembinaan Masyarakat Indonesia, Jalan Balai Desa Marindal II Pasar 12 Medan from June to September 2023. The research used a factorial Randomized Block Design, consisting of the first factor of the EMS induction application with 3 levels, namely E0 (without EMS as control), E1 (concentration 0.50%), E2 (concentration 0.70%), and the second factor was the provision of 2.4 kg cow manure compost/plot with 3 levels, namely I0 (no cow manure), I1 (1-week interval after planting), and I2 (2-week interval after planting). The parameters observed in this study included plant height (cm), flowering age (DAT), fruit weight persample (kg), and fruit weight perplots (kg). Diversity analysis used the ANOVA test and, if significantly different, continued with Duncan's Multiple Range Test (DMRT) at the 5% level. The research results showed that the EMS concentration at 12 WAP had a very significant effect on plant height, flowering age, fruit weight per sample, and fruit weight per plot, and the best EMS concentration was E2 (0.70%) by soaking the seeds for 3 hours. Two MST cow manure of 2.4 kg/plots had a very significant effect on plant height, flowering age, fruit weight persample, and fruit weight perplots. The interaction of the EMS mutation induction treatment and the dose of cow manure on cucumber plants had a very significant effect on plant height, flowering age, fruit weight per sample, and fruit weight per plot. Combination of E2I2 (0.70% immersion for 3 hours plus 2 WAP intervals at a dose of 2.4 kg/plots).